2009
DOI: 10.1177/1469787409343191
|View full text |Cite
|
Sign up to set email alerts
|

Gendered perceptions of learning and fairness when choice between exam types is offered

Abstract: Learning processes and strategies for assessing students in higher education have been studied from a variety of different angles. Numerous inventories measuring cognitive, affective, and connotative aspects of learning have been developed (Garcia and Pintrich, 1996;Geisler-Brenstein and Schmeck, 1996). Likewise, numerous studies have noted what types of test different students seem to prefer (for example, Zeidner, 1987) and which tests seem biased toward particular types of students (Bolger and Kellaghan, 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Compared to opportunity to learn, which typically considers fairness prior to assessment and which is closely aligned with instruction, the theme of access to demonstrate learningproviding students with "multiple, varied, equitable, and meaningful opportunities to demonstrate their learning" (Tierney, 2016, p.6)-has typically been characterized in terms of assessment opportunities that students are provided with to demonstrate what they know or can do (Camilli, 2006(Camilli, , 2013Cowie, 2015;Duffield & Spencer, 2002;Murillo & Hidalgo, 2017;Suskie, 2000;Tierney, 2013;Volante, 2006). The empirical studies have also demonstrated that students feel treated fairly when provided with multiple assessment opportunities (Duffield & Spencer, 2002;Mauldin, 2009). Similar to the last interpretation of opportunity to learn, equitable, differentiated, and multiple assessments of students are regarded fair in the opportunity to demonstrate learning theme.…”
Section: Opportunity For Learning and Access To Demonstrate Learningmentioning
confidence: 70%
“…Compared to opportunity to learn, which typically considers fairness prior to assessment and which is closely aligned with instruction, the theme of access to demonstrate learningproviding students with "multiple, varied, equitable, and meaningful opportunities to demonstrate their learning" (Tierney, 2016, p.6)-has typically been characterized in terms of assessment opportunities that students are provided with to demonstrate what they know or can do (Camilli, 2006(Camilli, , 2013Cowie, 2015;Duffield & Spencer, 2002;Murillo & Hidalgo, 2017;Suskie, 2000;Tierney, 2013;Volante, 2006). The empirical studies have also demonstrated that students feel treated fairly when provided with multiple assessment opportunities (Duffield & Spencer, 2002;Mauldin, 2009). Similar to the last interpretation of opportunity to learn, equitable, differentiated, and multiple assessments of students are regarded fair in the opportunity to demonstrate learning theme.…”
Section: Opportunity For Learning and Access To Demonstrate Learningmentioning
confidence: 70%
“…However, there are mixed results in the literature. As a prime instance, Mauldin (2009); Simkin and Kuechler (2005) and Weaver and Raptis (2001) examined performance of students in MC and CR tests and found no significant differences between male and female test takers. However, findings of this study suggested that males perform better in MC items while females do better in CR items.…”
Section: Discussionmentioning
confidence: 99%